Meta-analysis of fecal metagenomes reveals global microbial signatures that are specific for colorectal cancer - Wirbel, Jakob; Pyl, Paul Theodor; Kartal, Ece; Zych, Konrad; Kashani, Alireza; Milanese, Alessio; Fleck, Jonas S; Voigt, Anita Y; Palleja, Albert; Ponnudurai, Ruby; Sunagawa, Shinichi; Coelho, Luis Pedro; et al. (Nature medicine, 2019)
Association studies have linked microbiome alterations with many human diseases. However, they have not always reported consistent results, thereby necessitating cross-study comparisons. Here, a meta-analysis of eight geographically and technically diverse fecal shotgun metagenomic studies of colorectal cancer (CRC, n = 768), which was controlled for several confounders, identified a core set of 29 species significantly enriched in CRC metagenomes (false discovery rate (FDR) < 1 × 10-5). CRC signatures derived from single studies maintained their accuracy in other studies. By training on multiple studies, we improved detection accuracy and disease specificity for CRC. Functional analysis of CRC metagenomes revealed enriched protein and mucin catabolism genes and depleted carbohydrate degradation genes. Moreover, we inferred elevated production of secondary bile acids from CRC metagenomes, suggesting a metabolic link between cancer-associated gut microbes and a fat- and meat-rich diet. Through extensive validations, this meta-analysis firmly establishes globally generalizable, predictive taxonomic and functional microbiome CRC signatures as a basis for future diagnostics.
Keywords: Feces; druhová specificita; Male; kohortové studie; kolorektální nádory; metagenom; Cohort Studies; feces; Databases, Genetic; Aged; Gastrointestinal Microbiome; mužské pohlaví; senioři; reprodukovatelnost výsledků; Models, Biological; Species Specificity; střevní mikroflóra; Reproducibility of Results; databáze genetické; Metagenome; lidé; biologické modely; ženské pohlaví; Biomarkers, Tumor; Humans; Adenoma; Colorectal Neoplasms; adenom; Female; lidé středního věku; nádorové biomarkery; Middle Aged